Experimental Study on Consolidation Characteristics of Compacted Loess - Jinhua Li; Songwei Zhao; Xiong Wang; Jiaqi Hao; Bin Zhi; Hui Zhang; Botuan Deng (Advances in Civil Engineering)
The prediction of foundation settlement is an important topic in loess filling engineering. Based on a filled foundation in Yan’an, China, this study explores the consolidation characteristics of compacted loess with different compaction energy and consolidation pressure through consolidation tests, analyzes the strain-time curve and refines the curve within 2 h, separates the primary and secondary consolidations, and obtains the critical time point between the primary and secondary consolidations. Deformation rate St′ and cumulative deformation St were introduced to analyze the St′ − St curve at the secondary consolidation stage; the secondary consolidation coefficient was employed to describe the secondary consolidation characteristics of compacted loess. According to the secondary consolidation characteristics, a prediction model of loess settlement considering different compaction energy and fill thickness was proposed, and the applicability of the model was further analyzed. The model will facilitate in guiding the design and construction of loess filling engineering.